Differential physiological response of the grapevine varieties Touriga Nacional and Trincadeira to combined heat, drought and light stress - Carvalho, L.C. (2015)
Worldwide, extensive agricultural losses are attributed to drought, often in combination with heat in Mediterranean climate regions, where grapevine traditionally grows. The available scenarios for climate change suggest increases in aridity in these regions. Under natural conditions plants are affected by a combination of stresses, triggering synergistic or antagonistic physiological, metabolic or transcriptomic responses unique to the combination. However the study of such stresses in a controlled environment can elucidate important mechanisms by allowing the separation of the effects of individual stresses. To gather those effects, cuttings of two grapevine varieties, Touriga Nacional (TN) and Trincadeira (TR), were grown under controlled conditions and subjected to three abiotic stresses (drought – WS, heat – HS and high light – LS) individually and in combination two-by-two (WSHS, WSLS, HSLS) or all three (WSHSLS). Photosynthesis, water status, contents of H2O2, abscisic acid and metabolites of the ascorbate-glutathione cycle were measured in the leaves. Common and distinct response features were identiﬁed in the different stress combinations. Photosynthesis was not hindered in TN by LS, while even individual stresses severely affect photosynthesis in TR. Abscisic acid may be implicated in grapevine osmotic responses since it is correlated with tolerance parameters, especially in combined stresses involving drought. Overall, the responses to drought-including treatments were clearly distinct to those without drought. From the speciﬁc behaviours of the varieties, it can be concluded that TN shows a higher capacity for heat dissipation and for withstanding high light intensities, indicating better adjustment to warm conditions, provided that water supply is plentiful